Integrated drawing techniques designing interiors with hand sketching, sketchup, and photoshop - Gordon, Robert Philip (New York Fairchild Books, an imprint of Bloomsbury Publishing Inc., 2016)
"Since the appearance of simplified 3D sketching programs like SketchUp, architects and interior designers have been called on to use both freehand and 3D CAD drawings, often at very earliest stages of design. Since we must often go back and forth between analytical plan views and 3D visual views, it's important that this be a seamless process, requiring little disruptive action or break in the workflow. Drawing and Design for Residential Interiors closes the gap between creativity and geometry, teaching beginner architects and interior designers how to design their residential interiors using freehand sketching and computer-aided design simultaneously. From concept planning to 3D rendering, this book is a comprehensive guide to designing residences by hand and computer"-- Provided by publisher.
Machine generated contents note: -- Preface: Approach to the Book and Simultaneous Design -- Chapter 1: The Program -- Chapter 2: Site and Landscape -- Chapter 3: The Foyer: Entering the Home and Connecting the Elements -- Chapter 4: Living Space/Furniture -- Chapter 5: Dining Space -- Chapter 6: Food Preparations and the Kitchen -- Chapter 7: Combos and Adjacencies - Living/Dining/Kitchen "Great Room" -- Chapter 8: Bathing, Washing and the Toilet -- Chapter 9: Sleep Spaces, Dressing Areas and Storage -- Chapter 10: Home Workspaces -- Chapter 11: Combos and Adjacencies - Bathroom/Bedroom/Study Wing -- Chapter 12: House Ensembles -- Chapter 13: The Community: Urban Design -- Chapter 14: Presentations.
Includes index.
This book is in the Architecture Satellite LIbrary.
Prof. Jocelyn C. Pinzon (Recommending faculty) - Bookfair2017
Keywords: Architectural drawing -- Technique; Architectural drawing -- Data processing; Interior architecture -- Design; Interior decoration -- Design